(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
Background. Positive eﬀect of physical activity on mental health has been proven by scientifc research, whereas the quality of life scale is an important instrument for the assessment of the overall functioning of people with mental disorders. The aim of the study was to determine the relationship between the quality of life and physical activity in patients with depressive disorder. Methods. The survey involved randomly selected subjects (n = 38) with depression aged 20–75. The subjects were assessed using quality of life SF-36 and physical activity questionnaires. Results. The survey results showed that patients with mental disorders evaluated their physical health much better than mental health (p < .01). General health perception and social functioning improve with increasing energy and vitality. Subjects who were more physically active at home rated their general physical activity better in quality of life questionnaire. Conclusions. Higher physical activity at work has a positive inﬂuence on vitality and general health perception. Keywords: quality of life, physical activity, mental health.